Ferroptosis in Ovarian Cancer: A Novel Therapeutic Strategy - Li, Lanyu; Qiu, Cheng; Hou, Min; Wang, Xinyu; Huang, Changzhen; Zou, Jialin; Liu, Tianyi; Qu, Jinfeng (Frontiers in Oncology, 2021)
Ovarian cancer (OVCA) is one of the most lethal malignancies with a five-year relative survival below 50% by virtue of its high recurrence rate and inadequate early detection methods. For OVCA patients, modern approaches include debulking surgery, chemotherapies, angiogenesis inhibitors, poly ADP-ribose polymerase (PARP) inhibitors, and immunotherapies depending on the histological type and staging of the tumor. However, in most cases, simple standard treatment is not satisfactory. Thus, a more effective way of treatment is needed. Ferroptosis is a newly recognized type of regulated cell death marked by lipid peroxidation, iron accumulation and glutathione deprivation, having a connection with a variety of disorders and showing great potential in anti-tumor therapy. Intriguingly, a possible connection between ferroptosis and OVCA is shown on the basis of previously published findings. Furthermore, a growing number of ferroptosis protection pathways have been identified during the past few years with increasing ferroptosis regulators being discovered. In this review, we summarized several major pathways involved in ferroptosis and the study foundation of ferroptosis and ovarian cancer, hoping to provide clues regarding OVCA treatment. And some important issues were also raised to point out future research directions.